Strut effectiveness factor and maximum shear strength of Infra Lightweight Concrete (ILC). (1st July 2023) - Elshahawi, Mahmoud; Hückler, Alex; Schlaich, Mike
Highlights: The maximum shear strength of ILC beams with stirrups was experimentally investigated. The effective compressive strength of shear cracked ILC struts was experimentally estimated. The ILC's strut effectiveness factor βs was experimentally estimated as 0.83. Abstract: Infra Lightweight Concrete (ILC) is a versatile construction material that is characterized by its substantial lightweight (dry density ≤ 800 kg/m 3 ), an excellent heat insulation and a sufficient bearing strength. Given these properties, ILC has been presented as a promising approach for modern building envelops, offering a viable alternative to conventional building façades. This implies that composite exterior walls combining a bearing element and several insulating layers can be efficiently replaced by a single ILC layer. This replacement offers several advantages related to building sustainability and allows architectural innovation. The first realistic mix and the first ILC building date back to less than two decades. Since that time, ILC has built a solid reputation among ecologically aware designers. Therefore, many successful mixes were developed, resulting in a significant improvement of its mechanical properties. Also, several studies have been conducted to understand its structural behaviour, including studies on its bond, compressive, flexural and, most recently, shear behaviour. One of the key challenges revealed by these studies is the ILC high brittleness and moderate strength, both hindering in most cases the full development of reinforcement strength, thereby, limiting the capacity of reinforced ILC sections. This work experimentally handles the shear strength limit of ILC beams with web stirrups. This limitation was frequently set to preclude the compressive failure of inclined struts prior to the development of web stirrups capacity. Five ILC beams made of five ILC mixes were tested in a 4-point bending test, with beams configuration and test setups were adapted to push the failure to the crushing of inclined struts by excessive compression. The equalization of experimental to theoretical strength of inclined strut assisted in obtaining the ILC' strut effectiveness factor (βs = 0.83). The maximum shear strength was, then, linked to the strut capacity that is directly related to the ILC strength and the estimated βs.